B(C6F5)3-Catalyzed site-selective N1-alkylation of benzotriazoles with diazoalkanes. Issue 63 (13th July 2021) - Zhao, Yunbo; Mandal, Dipendu; Guo, Jing; Wu, Yile; Stephan, Douglas W.
Abstract : The site-selective N 1 -alkylation of benzotriazoles with diazoalkanes is achieved using 10 mol% of B(C6 F5 )3 as a catalyst. Abstract : Alkylation of benzotriazoles is synthetically challenging, often leading to mixtures of N 1 and N 2 alkylation. Herein, metal-free catalytic site-selective N 1 -alkylation of benzotriazoles with diazoalkanes is described in the presence of 10 mol% of B(C6 F5 )3 . These reactions provide N 1 -alkylated benzotriazoles in good to excellent yields and this protocol is successfully adapted to gram-scale syntheses as well as a derivative with antimicrobial activity.